(untitled) (Pragyaratna प्रज्ञारत्न, 2024)
This paper explores meso-level policy actors’ familiarity, engagement and perception in relation to the implementation of multilingual education in Nepal. The data were gathered through a census survey conducted online with the education officers (here known as meso-level policy actors) working at Education Sections of municipal levels across Nepal. A total of 163 respondents fully completed the online survey that explores how familiar they are with multilingual education, what they have been doing (or have done) and what they think is important for the implementation of multilingual education in Nepal. The findings revealed that the policy actors’ engagement and familiarity with the national policy on multilingual education is below the average, indicating that policy communication and understanding in the implementation of multilingual education in Nepal’s schools is inadequate. The findings also revealed that the policy actors’ engagement is not focused on understanding multilingualism as a regular pedagogical process rather the attention has been diverted towards teaching local languages/mother tongues separately as subjects, ultimately reproducing the monolingual ideologies in education. This implies that a holistic understating is needed for the successful implementation of multilingual education policy in Nepal.